Evaluasi Penerapan Gamification pada Keterlibatan Karyawan di Sistem Informasi Sumber Daya Manusia - Prakoso, Bayu Adi; Fabroyir, Hadziq (Syntax Literate, 2025)
The COVID-19 pandemic has led to significant changes in the work environment, including an increase in remote work, negatively impacting employee engagement. Various approaches have been attempted to address this issue, including gamification, which shows great potential in enhancing employee engagement. This study aims to evaluate the implementation of gamification in Human Resource Information Systems (HRIS) to improve employee engagement. The methodology used in this research involves two iterations of Design Thinking, where the first iteration focuses on developing features based on the eight core drives of the Octalysis framework. In contrast, the second iteration examines the phases of the user journey. The research process includes in-depth interviews, usability testing, and employee engagement measurement using the Utrecht Work Engagement Scale (UWES). The research findings indicate that well-designed gamification elements can significantly enhance energy (vigor) but do not affect on the dimensions of dedication and full engagement (absorption) among employees, providing critical insights for management to create a more productive and engaging work environment.